2009
DOI: 10.1016/j.mrfmmm.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis in vivo in T cells of p21-deficient mice

Abstract: Mice that are deficient in p53 exhibit an early onset of multiple types of tumors, especially thymic lymphoma. However, it remains unclear to what extent each of the p53-regulated pathways exerts its tumor suppressor activity. p21Cip1/Waf1, acting down stream of p53, is a major G1/S checkpoint protein that restricts cell cycle progression into S phase in the presence of DNA damage. While at old ages p21−/− mice have a higher incidence of many types of tumors than p21+/+ mice, they are more resistant to thymic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the other hand, studies focused on the role of p21 in ATM-mediated signal pathways have shown that p21 is a downstream effector of ATM-mediated growth control, and have suggested that loss pf p21 in Atm -deficient mice results in a delay in thymic lymphomagenesis and in an apparent increase in spontaneous apoptosis in tumor cells [ 25 , 26 ]. This indicates that the loss of p21 function might have tumor suppression consequences.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies focused on the role of p21 in ATM-mediated signal pathways have shown that p21 is a downstream effector of ATM-mediated growth control, and have suggested that loss pf p21 in Atm -deficient mice results in a delay in thymic lymphomagenesis and in an apparent increase in spontaneous apoptosis in tumor cells [ 25 , 26 ]. This indicates that the loss of p21 function might have tumor suppression consequences.…”
Section: Discussionmentioning
confidence: 99%